2015
DOI: 10.4209/aaqr.2015.10.0608
|View full text |Cite
|
Sign up to set email alerts
|

Biological Toxicities of Exhausts from a Diesel-Generator Fueled with Water-Containing Acetone/Butanol and Waste-Edible-Oil-Biodiesel Blends

Abstract: In this investigation, conventional diesel (D), 1-30 vol% waste-edible-oil-biodiesel (WEO-biodiesel, (W), 1-3 vol% pure/water-containing acetone (A/A'' (5% water content)) or 1-50 vol% butanol (B/B' (2% water content)/B'' (5% water content) were tested as fuels and their effects on the cytotoxicity of emissions from a generator at 3 kW load were studied. Human male single cells (U937) and the MTT (3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide) method were used to test the cell toxicity of gas-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It was found that watercontaining and -free butanol-added WEO-biodiesel yielded 21.7-56.3% less PM, 28.7-63.8% less PM-EC, 11.8-48.7% less PM-OC, 23.5-59.2% less total-PAHs, and 37.0-55.3% less total-BaP eq than fossil diesel (Tsai et al, 2015a). And the cytotoxicity tests revealed that adding 1-3% acetone/watercontaining acetone to bio-dieselhols reduced the mortality of U937 that were exposed to exhaust emissions organic-solvent extraction of to U937 when the generator was loaded at 3 kW (Tsai et al, 2015b). To study further the influence of adding biodiesel to traditional petro-diesel (as D100) on the emission factors (EFs) of POPs (PCDD/Fs, PCBs, PBDD/Fs, and PBDEs) from a diesel-generator that was fuelled with different fuel blends were explored; in this investigation, D100 is blended with 20 and 40 vol% WOC-biodiesel (W20 and W40) to form alternative fuels for use in diesel engine generators.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that watercontaining and -free butanol-added WEO-biodiesel yielded 21.7-56.3% less PM, 28.7-63.8% less PM-EC, 11.8-48.7% less PM-OC, 23.5-59.2% less total-PAHs, and 37.0-55.3% less total-BaP eq than fossil diesel (Tsai et al, 2015a). And the cytotoxicity tests revealed that adding 1-3% acetone/watercontaining acetone to bio-dieselhols reduced the mortality of U937 that were exposed to exhaust emissions organic-solvent extraction of to U937 when the generator was loaded at 3 kW (Tsai et al, 2015b). To study further the influence of adding biodiesel to traditional petro-diesel (as D100) on the emission factors (EFs) of POPs (PCDD/Fs, PCBs, PBDD/Fs, and PBDEs) from a diesel-generator that was fuelled with different fuel blends were explored; in this investigation, D100 is blended with 20 and 40 vol% WOC-biodiesel (W20 and W40) to form alternative fuels for use in diesel engine generators.…”
Section: Introductionmentioning
confidence: 98%
“…The higher oxygen content of biodiesels than petroleum diesel can produce more complete combustion and lower the emissions of CO, PM, HC and persistent organic pollutants (Raheman and Ghadge, 2007;Özener et al, 2014). Additionally, the lower sulfur and almost no aromatic compositions could reduce the SO 2 and POP emissions from the diesel engine and further reduce the potential of secondary fine particle formation (Tsai et al, 2015). The safety of storage and transport could also be enhanced by the higher flash point of biodiesel than that of fossil fuel (Li et al, 2016;de Mello et al, 2017).…”
Section: Biodiesel Development Application and Their Emissionsmentioning
confidence: 94%
“…Diesel engines have the advantages including high efficiency, a high level of fuel economy with great torque output, high durability and reliability, and low operating costs. Diesel engines are major source of emissions including particulate matter (PM), nitrogen oxides, sulfur oxides, total hydrocarbons, carbon dioxide, carbon monoxide as well as toxic chemicals such as polycyclic aromatic hydrocarbons Tsai et al, 2015). However, it is well known that PM emissions from diesel engines are are relatively high, due to the combustion of heterogeneous mixture in the cylinder at higher combustion temperatures (Saxena and Maurya, 2016).…”
Section: Introductionmentioning
confidence: 99%